Efficacy and safety of amantadine for the treatment of L-DOPA-induced dyskinesia - Pérez Lloret, Santiago (2018)
l-DOPA induced dyskinesias (LIDs) may affect up to 40% of Parkinson’s disease (PD) and impact negatively health-related quality of life. Amantadine has demonstrated significant antidyskinetic effects in animal PD models and in randomized double-blind placebo-controlled trials (RCTs) in patients with PD. These effects are thought to be related to the blockade of NMDA receptors modulating cortico-striatal glutamatergic–dopaminergic interactions involved in the genesis of LIDs. There are three pharmaceutical forms of amantadine currently available in the market: an oral immediate-release (IR) formulation, which is widely available; an extended-release (ER) formulation (ADS-5102) which has been recently developed and approved by the FDA; and an intravenous infusion (IV) solution, which is not commonly used in clinical practice. RCTs with amantadine IR or ER, involving more than 650 patients have shown consistent and long-lasting reductions in LIDs. Interestingly, ADS-5102 not only reduced LIDs, but also reduced significantly at the same time the duration of daily OFF-time, a unique finding compared with other antiparkinsonian medications that usually reduce time spent OFF at the cost of worsening of LIDs. Amantadine IR might also have possible effects on other PD symptoms such as apathy or fatigue. The most common adverse reactions with amantadine are constipation, cardiovascular dysfunction including QT prolongation, orthostatic hypotension and edema, neuropsychiatric symptoms such as hallucinations, confusion and delirium, nausea and livedo reticularis. Corneal degeneration is rare but critical. In summary, amantadine immediate and extended-release are effective and safe for the treatment of LIDs.